Cost-effectiveness of myopia-control spectacles and contact lenses for children and adolescents in Wales - Hayley Bennett; Andy Britton; David O’Sullivan; Francesca Lado (Cost Effectiveness and Resource Allocation)
Abstract Background Early intervention to slow childhood progression of myopia may improve quality of life and prevent future complications that burden individuals and healthcare systems. This study assessed the cost-effectiveness of myopia-control spectacles and contact lenses for the reduction of myopia progression among children and adolescents in Wales. Methods A cost-utility analysis compared peripheral plus spectacle lenses (PPSL), multifocal soft contact lenses (MFSCL) and orthokeratology against single-vision correction. Efficacy and safety were informed by a Cochrane systemic review and meta-analyses. Quality-adjusted life years (QALYs) and costs incurred by NHS Wales were modelled over a lifetime horizon and discounted at 3.5%. Sensitivity analyses estimated uncertainty in incremental cost-effectiveness ratios (ICERs). Results PPSL was estimated to provide minimal benefit at a higher cost than single-vision correction. MFSCL gave a 0.28 QALY improvement at an additional cost of £4,040; corresponding to an ICER of £8,367 versus single-vision correction. Orthokeratology provided 0.5 QALYs at an additional cost of £3,732; corresponding to an ICER of £3,995 versus single-vision correction. In probabilistic sensitivity analysis, ICERs were below £20,000 in 71% and 90% of simulations for MFSCL and orthokeratology, respectively. Orthokeratology was the most cost-effective strategy in 76% of simulations. Cost-effectiveness was influenced by changes in progression rates, intervention costs and the utility of high myopia. However, orthokeratology remained the most cost-effective strategy throughout. Conclusions MFSCL and orthokeratology may be cost-effective options to slow the progression of myopia at thresholds applied in the UK. Further research is needed to understand the long-term effects of myopia-control interventions and their impact on quality of life.